2006
DOI: 10.1093/jac/dki492
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and evolution of blaZ from Staphylococcus aureus and coagulase-negative staphylococci

Abstract: Results indicated a separate evolution for plasmid- and chromosomally-encoded blaZ. Although a common gene pool seems to exist among staphylococci, exchange of blaZ between strains and species is judged to be an extremely rare event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
154
2
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(175 citation statements)
references
References 39 publications
12
154
2
7
Order By: Relevance
“…The frequency of blaZ described here was higher than the 18.4% reported by Sawant et al (2009) but lower than the 100% observed in penicillin resistant S. aureus from Denmark (Vesterholm-Nielsen et al 1999). The results indicate that beta-lactamase production encoded by blaZ might be the main mechanism associated with resistance to beta-lactams in staphylococci causing mastitis in goats and sheep in Brazil, as previously reported in other countries for dairy cattle (Olsen et al 2006). …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The frequency of blaZ described here was higher than the 18.4% reported by Sawant et al (2009) but lower than the 100% observed in penicillin resistant S. aureus from Denmark (Vesterholm-Nielsen et al 1999). The results indicate that beta-lactamase production encoded by blaZ might be the main mechanism associated with resistance to beta-lactams in staphylococci causing mastitis in goats and sheep in Brazil, as previously reported in other countries for dairy cattle (Olsen et al 2006). …”
Section: Discussionsupporting
confidence: 82%
“…Transfer of beta-lactam resistance genes may occur among human and animal Staphylococcus spp. isolates and is a public health concern (Vesterholm-Nielsen et al 1999, Katayama et al 2005, Olsen et al 2006. Caution should be exercised in regard to raw milk ingestion, which is a common practice in rural areas under development.…”
Section: Discussionmentioning
confidence: 99%
“…All the isolates were tested for the presence of blaZ gene (coding for β-lactamase) by polymerase chain reaction (PCR) with forward primer 5'-TAA GAG ATT TGC CTA TGC TT-3' and reverse primer 5'-TTA AAG TCT TAC CGA AAG CAG-3' (Olsen et al, 2006). DNA extraction was carried out using the ChargeSwitch DNA Mini Bacteria Kit (Invitrogen, USA) according to the manufacturer's instructions for staphylococci.…”
Section: Pcr Characterizationmentioning
confidence: 99%
“…La resistencia a la penicilina se explica por la inactivación del fármaco (hidrolización del anillo beta-lactámico) a través de la producción de una enzima conocida como beta-lactamasa, la cual es codificada por el gen blaZ, que hace parte de un elemento transportable localizado en un plásmido que, usualmente, confiere resistencia a otros antibióticos (35). La expresión del gen blaZ está condicionada por dos genes reguladores blaR1 (antirrepresor) y blaI (represor).…”
Section: Mecanismos De Resistencia Antibiótica Del S Aureusunclassified